Bruchmechanisches Schnittebenenkonzept zur lebensdauergerechten Auslegung von hyperelastischen Klebverbindungen bei multiaxialen und variablen Belastungsamplituden - Buczek, Moritz; Duffe, Tobias; Kullmer, Gunter; Tews, Karina; Teutenberg, Dominik; Meschut, Gerson (25. Kolloquium: Gemeinsame Forschung in der Klebtechnik)

Consideration of residual stresses and damage in the fracture mechanical investigation of mechanically joined structures - Weiß, Deborah; Duffe, Tobias; Joy, Tintu David; Kullmer, Gunter (Materials Research Proceedings)
Abstract. The process of joining is used in numerous sectors of the manufacturing industry, where constructions composed of individual components or metal sheets are combined to form complex structures. A straightforward and pervasive approach for joining materials of disparate natures and coated surfaces is clinching. During the clinching process, plastic deformation, residual stresses and damage are introduced into the joint. Due to time-varying service loads cracks can initiate and propagate in the vicinity of the joint which limits the lifetime of the clinched structure. In order to prevent those damage cases, it is crucial to perform fracture mechanical evaluation of cracks in the joint region. Therefore, this publication deals with the question of how plastic deformation, residual stresses and damage need to be considered for the assessment of a crack. For this purpose, simple substitute models are employed to illustrate the principles based on the clinching application example.

Experimentelle Ermittlung von Rissablenkungswinkeln bei außerphasiger Mixed-Mode-Belastung mittels einer neuartigen Probengeometrie - Weiß, Deborah; Krome, Sven; Duffe, Tobias; Kullmer, Gunter; Ostwald, Richard

BESCHREIBUNG DES R- UND DES TEMPERATUREINFLUSSES SOWIE DES EINLAUFVERHALTENS BEI EXPERIMENTELL BESTIMMTEN RISSFORTSCHRITTSKURVEN MIT DEM EXPONENTIALANSATZ - Kullmer, Gunter; Weiß, Deborah; Duffe, Tobias; Schramm, Britta; Ostwald, Richard

An alternative and robust formulation of the fatigue crack growth rate curve for long cracks - Kullmer, Gunter; Weiß, Deborah; Schramm, Britta (Engineering Fracture Mechanics)
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Weiterentwicklung des Exponentialansatzes zur Beschreibung von Rissfortschrittskurven - Kullmer, Gunter; Weiß, Deborah; Schramm, Britta

Bruchmechanische Untersuchung des Dualphasenstahls HCT590X unter Temperatureinfluss - Weiß, Deborah; Duffe, Tobias; Buczek, Moritz; Kullmer, Gunter; Schramm, Britta

Fracture mechanical investigation of preformed metal sheets using a novel CC-specimen - Weiß, Deborah; Schramm, Britta (Procedia Structural Integrity)
Keywords: General Engineering; Energy Engineering and Power Technology

Stiffness optimization and reliable design of a hip implant by using the potential of additive manufacturing processes - Risse, Lena; Woodcock, Steven Clifford; Brüggemann, Jan-Peter; Kullmer, Gunter; Richard, Hans Albert (BioMedical Engineering OnLine)
Abstract Background Due to the steadily increasing life expectancy of the population, the need for medical aids to maintain the previous quality of life is growing. The basis for independent mobility is a functional locomotor system. The hip joint can be so badly damaged by everyday wear or accelerated by illness that reconstruction by means of endoprostheses is necessary. Results In order to ensure a high quality of life for the patient after this procedure as well as a long service life of the prosthesis, a high-quality design is required, so that many different aspects have to be taken into account when developing prostheses. Long-term medical studies show that the service life and operational safety of a hip prosthesis by best possible adaptation of the stiffness to that of the bone can be increased. The use of additive manufacturing processes enables to specifically change the stiffness of implant structures. Conclusions Reduced implant stiffness leads to an increase in stress in the surrounding bone and thus to a reduction in bone resorption. Numerical methods are used to demonstrate this fact in the hip implant developed. The safety of use is nevertheless ensured by evaluating and taking into account the stresses that occur for critical load cases. These results are a promising basis to enable longer service life of prostheses in the future.
Keywords: Radiology; Nuclear Medicine and imaging; Biomedical Engineering; General Medicine; Biomaterials; Radiological and Ultrasound Technology

Methodenentwicklung zur numerischen Lebensdauerprognose von hyperelastischen Klebverbindungen infolge zyklischer Beanspruchung mittels bruchmechanischer Ansätze - Tews, Karina; Aubel, Tobias; Teutenberg, Dominik; Meschut, Gerson; Duffe, Tobias; Kullmer, Gunter (22. Kolloquium: Gemeinsame Forschung in der Klebtechnik)

Bewertung der Knochen-Schraube Verbindung im Auszugtest und unter physiologischer Belastung in der Finite Elemente Methode - Woodcock, Steven Clifford; Schramm, Britta; Kullmer, Gunter; Richard, Hans Albert

Global energy release rate of small penny-shaped cracks in hyperelastic materials under general stress conditions - Duffe, Tobias; Kullmer, Gunter; Tews, Karina; Aubel, Tobias; Meschut, Gerson (Theoretical and Applied Fracture Mechanics)

Fracture mechanical concept to predict crack nucleation in elastic adhesive joints - Duffe, Tobias; Tews, Karina; Kullmer, Gunter; Meschut, Gerson (ECF23, European Conference on Fracture 2022)

Numerische Lebensdauerprognose von hyperelastischen Klebverbindungen mit einem bruchmechanischen Ansatz - Duffe, Tobias; Tews, Karina; Aubel, Tobias; Meschut, Gerson; Kullmer, Gunter (Fachzeitschrift für Schweißen und verwandte Verfahren)

Further Development of 3D Crack Growth Simulation Program to Include Contact Loading Situations - Joy, Tintu David; Weiß, Deborah; Schramm, Britta; Kullmer, Gunter (Applied Sciences)
Crack growth in structures depends on the cyclic loads applied on it, such as mechanical, thermal and contact, as well as residual stresses, etc. To provide an accurate simulation of crack growth in structures, it is of high importance to integrate all kinds of loading situations in the simulations. Adapcrack3D is a simulation program that can accurately predict the propagation of cracks in real structures. However, until now, this three-dimensional program has only considered mechanical loads and static thermal loads. Therefore, the features of Adapcrack3D have been extended by including contact loading in crack growth simulations. The numerical simulation of crack propagation with Adapcrack3D is generally carried out using FE models of structures provided by the user. For simulating models with contact loading situations, Adapcrack3D has been updated to work with FE models containing multiple parts and necessary features such as coupling and surface interactions. Because Adapcrack3D uses the submodel technique for fracture mechanical evaluations, the architecture of the submodel is also modified to simulate models with contact definitions between the crack surfaces. This paper discusses the newly implemented attribute of the program with the help of illustrative examples. The results confirm that the contact simulation in Adapcrack3D is a major step in improving the functionality of the program.
Keywords: Fluid Flow and Transfer Processes; Computer Science Applications; Process Chemistry and Technology; General Engineering; Instrumentation; General Materials Science

Influence of plane mixed-mode loading on the kinking angle of clinchable metal sheets - Weiß, Deborah; Schramm, Britta; Kullmer, Gunter (Procedia Structural Integrity)
Keywords: General Engineering; Energy Engineering and Power Technology

Development of a method for the separate measurement of the growth of internal crack tips by means of the potential drop method - Kullmer, Gunter; Weiß, Deborah; Schramm, Britta (Engineering Fracture Mechanics)
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Fracture mechanical evaluation of the material HCT590X - Schramm, Britta; Weiß, Deborah (Materials Testing)
For a reliable, strength-compliant and fracture-resistant design of components and technical structures and for the prevention of damage cases, both the criteria of strength calculation and fracture mechanics are essential. In contrast to strength calculation the fracture mechanics assumes the existence of cracks which might further propagate due to the operational load. First, the present paper illustrates the general procedure of a fracture mechanical evaluation of fatigue cracks in order to assess practical damage cases. Fracture mechanical fundamentals which are essential for the calculation of the stress intensity factors K I and the experimental determination of fracture mechanical material parameters (e.g. threshold Δ K I,th against fatigue crack growth, crack growth rate curve) are explained in detail. The subsequent fracture mechanical evaluation on the basis of the local stress situation at the crack tip and the fracture mechanical material data is executed for different materials and selected crack problems. Hereby, the main focus is on the material HCT590X as it is the essential material being investigated by TRR285.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

A Review on the Modeling of the Clinching Process Chain - Part I: Design Phase - Schramm, Britta; Martin, Sven; Steinfelder, Christian; Bielak, Christian Roman; Brosius, Alexander; Meschut, Gerson; Tröster, Thomas; Wallmersperger, Thomas; Mergheim, Julia (Journal of Advanced Joining Processes)
Keywords: Mechanical Engineering; Mechanics of Materials; Engineering (miscellaneous); Chemical Engineering (miscellaneous)

A Review on the Modeling of the Clinching Process Chain - Part II: Joining Process - Schramm, Britta; Friedlein, Johannes; Gröger, Benjamin; Bielak, Christian Roman; Bobbert, Mathias; Gude, Maik; Meschut, Gerson; Wallmersperger, Thomas; Mergheim, Julia (Journal of Advanced Joining Processes)
Keywords: Mechanical Engineering; Mechanics of Materials; Engineering (miscellaneous); Chemical Engineering (miscellaneous)